An association study of ABCG2 rs2231142 on the concentrations of allopurinol and its metabolites. Issue 8 (10th June 2022) - Pilon, Marc‐Olivier; Leclair, Grégoire; Oussaïd, Essaïd; St‐Jean, Isabelle; Jutras, Martin; Gaulin, Marie‐Josée; Mongrain, Ian; Busseuil, David; Rouleau, Jean Lucien; Tardif, Jean‐Claude; Dubé, Marie‐Pierre; de Denus, Simon
Abstract: ABCG2 is a gene that codes for the human breast cancer resistance protein (BCRP). It is established that rs2231142 G>T, a single nucleotide polymorphism of the ABCG2 gene, is associated with gout and poor response to allopurinol, a uric acid‐lowering agent used to treat this condition. It has also been suggested that oxypurinol, the primary active metabolite of allopurinol, is a substrate of the BCRP. We thus hypothesized that carrying the rs2231142 variant would be associated with decreased oxypurinol concentrations, which would explain the lower reduction in uric acid. We performed a cross‐sectional study to investigate the association between the ABCG2 rs2231142 variant and oxypurinol, allopurinol, and allopurinol riboside concentrations in 459 participants from the Montreal Heart Institute Hospital Cohort. Age, sex, weight, use of diuretics, and estimated glomerular filtration rate were all significantly associated with oxypurinol plasma concentration. No association was found between rs2231142 and oxypurinol, allopurinol and allopurinol riboside plasma concentrations. Rs2231142 was not significantly associated with daily allopurinol dose in the overall population, but an association was observed in men, with T carriers receiving higher doses. Our results do not support a major role of ABCG2 in the pharmacokinetics of allopurinol or its metabolites. The underlying mechanism of the association between rs2231142 and allopurinol efficacy requires further investigation.